Sandbox Modeling of Transrotational Tectonics With Changeable Poles: Implications for the Yinggehai Basin - Liu, Jun; Jia, Dong; Yin, Hongwei; Shen, Li; Fan, Xiaogen; He, Zhiyuan; Cui, Jian; Yang, Shuang; Zhang, Yong (Frontiers in Earth Science, 2021)
The main formation of the Yinggehai Basin has been related to the rotation of the Indochina block, resulting in large-scale strike-slip motion along the Red River Fault Zone (RRFZ). Transrotational tectonics played a key role in the evolution of the Yinggehai Basin. In this study, we present analog experiments with a preexisting basal velocity discontinuity boundary, rotation of crustal blocks concerning vertical axes, and syntectonic sedimentations to evaluate how the transrotational tectonics controls the evolutionary process of the Yinggehai Basin. Particle image velocimetry (PIV) was used to monitor the deformation of the model surface. Four successive poles of rotation have been applied to the model. The basin evolution underwent two phases. An early phase of deformation is characterized by the nucleation of the main internal faults above the velocity discontinuity boundary and segmented en echelon border fault systems. In the early phase, the internal and boundary faults mainly accommodated large-scale strike-slip displacement. During progressive extension, the main internal faults deactivated, and tectonic activity is localized along the boundary and secondary internal faults in the late phase. The boundary faults in the rotating block play a dominant role in the widening and deepening of the rift zone at an accelerating rate. The model surface morphology shows similarities to the Yinggehai Basin, which is wide in the middle and converges toward the northwest and southeast. In addition, experimental profiles have been compared with seismic profiles in the Yinggehai Basin. The model results also indicate that the rotation of the Indochina block combines with strong strike-slip motion. The similarities between modeling and nature provide support for ∼250 km sinistral displacement along the RRFZ between ∼32 and ∼21 Ma.